Common Environmental Factors May Underpin the Comorbidity Between Generalized Anxiety Disorder and Mood Disorders via Activated Nitro-oxidative Pathways - Roomruangwong, Chutima; Simeonova, Denitsa S.; Stoyanov, Drozdstoy S.; Anderson, George; Carvalho, Andre; Maes, Michael (Current Topics in Medicinal Chemistry, 2018)
Generalized Anxiety Disorder (GAD) commonly co-occurs with mood disorders, especially Major Depressive Disorder (MDD) and bipolar disorder (BD), which are accompanied by activated neuro-immune and neuro-oxidative pathways. The aim of this narrative review is to review the phenomenological similarities and dissimilarities and the shared pathways between GAD and mood disorders. We searched PubMed, Scopus, and Google Scholar for articles published in English from 1980 to present. GAD and mood disorders, either MDD or BD, show some phenomenological overlaps and a high degree of comorbidity, especially between GAD and MDD. Both GAD and mood disorders are also frequently comorbid with other anxiety disorders, substance use disorders and medical conditions, including cardio- vascular disorder (CVD). Mood disorders have a worse prognosis when GAD is present. GAD and mood disorders are associated with female sex and may partly share genetic variants of risk. Moreover, both GAD and mood disorders frequently share similar environmental risks factors including Early Life Time Trauma (ELT) and Psychological Stressors in Adulthood (PSA). Increased nitro-oxidative stress and lipid peroxidation coupled to lowered lipid-associated antioxidant defenses are evident in GAD, MDD and type I bipolar patients. Patients with comorbid GAD and MDD show significantly higher nitro- oxidative biomarkers as compared with patients presenting with either GAD or MDD as well as patients with BD with or without co-occurring GAD. Activated immune-inflammatory processes characterized by increased levels of CRP and pro-inflammatory cytokines are other shared pathways that underpin GAD and mood disorders. Moreover, these pathways may explain comorbidities with medical disorders including CVD. Aberrations in HPA-axis, GABA and glutamate neurotransmission, NMDA and mu opioid-receptors and neuroimaging fields have yielded more inconsistent findings. In conclusion, here we propose a new model explaining GAD and the comorbidity between GAD and mood disorders. Common triggers such as ELT/PSA may underpin GAD and its comorbidity with mood disorders via activated neuro-oxidative, neuro-nitrosative and neuro-immune pathways.
Keywords: Depression